PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PENDIDIKAN PANCASILA DI KELAS V SD N 1 TAMBAKSOGRA - Hana Prasi Nur Alfiana; Agung Nugroho (STKIP Subang, 2024)
This study aims to enhance students' motivation and academic achievement through the implementation of the Make A Match cooperative learning model. The subjects of this study are 28 Grade V students at SD N 1 Tambaksogra. Method: This research is conducted as a classroom action research project, carried out over two cycles, with each cycle consisting of one session. Data collection methods include tests, questionnaires, observation, and documentation. Results: The study's findings indicate an increase in student motivation through the application of the Make A Match cooperative learning model, with an average score of 72% in the first cycle and an increase to an average of 87% in the second cycle. In terms of academic achievement, the percentage of students who achieved mastery increased from 60.71% in the first cycle to 85.71% in the second cycle.